Knowledge, Attitude, and Practices Associated With COVID-19 Among Healthcare Workers in Hospitals: A Cross-Sectional Study in India - Gopalakrishnan, Shivkumar; Kandasamy, Sangeetha; Abraham, Bobby; Senthilkumar, Monika; Almohammed, Omar A. (Frontiers in Public Health, 2021)
SARS-CoV-2 pandemic has caused phenomenal loss of lives and overburdened the health system in India. Low morale, fatigue and inadequate knowledge among healthcare workers (HCWs) are perceived threats to pandemic control. We aimed to assess the COVID-19 related level of Knowledge, Attitude and Practices (KAP) among our HCWs. A cross-sectional, electronically distributed, questionnaire-based study was conducted which identified HCWs’ demographics and the current KAP related to COVID-19. Descriptive statistics were used to present the participants’ demographics and Chi-square test was used to assess differences in KAP among participants. Of 1,429 total participants, 71.9% belonged to age group 21-40 years. Only 40.2% received any infection control training and 62.7% relied upon single source of information update. However, 82.9% of participants had adequate knowledge. Being married, urban dwelling and higher qualification were associated with knowledge adequacy (p<0.001). Interestingly, senior HCWs (age 41-50 years) were least likely to have adequate knowledge (74.1%). About 84% had positive attitude towards COVID-19, but 83.8% of participants feared providing care to COVID-19 patients. However, 93% of HCWs practiced safety precautions correctly most of the times and training had no influence on practice. In conclusion, more than 80% of HCWs in the study had adequate knowledge, positive attitude and practiced safely most of the time. However, pitfalls like poor training, knowledge uncertainties and fear of disease acquisition among HCWs need to be addressed.